2022
DOI: 10.3389/fimmu.2022.1043738
|View full text |Cite
|
Sign up to set email alerts
|

A novel oxidative stress- and ferroptosis-related gene prognostic signature for distinguishing cold and hot tumors in colorectal cancer

Abstract: Oxidative stress and ferroptosis exhibit crosstalk in many types of human diseases, including malignant tumors. We aimed to develop an oxidative stress- and ferroptosis-related gene (OFRG) prognostic signature to predict the prognosis and therapeutic response in patients with colorectal cancer (CRC). Thirty-four insertion genes between oxidative stress-related genes and ferroptosis-related genes were identified as OFRGs. We then performed bioinformatics analysis of the expression profiles of 34 OFRGs and clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…32,33 Recent studies have attempted to use multi-gene panels in CRC but highlighted the need for more sophisticated, integrative approaches. 34,35 Our study aligns with the growing trend of utilizing machine learning in oncological prognostication. PCDS, as shown in our research, outperform traditional methods like multivariate Cox regression.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…32,33 Recent studies have attempted to use multi-gene panels in CRC but highlighted the need for more sophisticated, integrative approaches. 34,35 Our study aligns with the growing trend of utilizing machine learning in oncological prognostication. PCDS, as shown in our research, outperform traditional methods like multivariate Cox regression.…”
Section: Discussionsupporting
confidence: 76%
“…These models often fail to account for interactions and pathway crosstalk, thus limiting their prognostic utility 32,33 . Recent studies have attempted to use multi‐gene panels in CRC but highlighted the need for more sophisticated, integrative approaches 34,35 …”
Section: Discussionmentioning
confidence: 99%
“…At the same time, varying levels of oxidative stress can also alter phosphorylation levels, thereby regulating the malignancy and prognosis of malignant tumors 28 . Some researchers have proposed that oxidative stress may be associated with the expression of ferritin metabolism genes, thereby interfering with prognosis 29 . Animal model experiments have shown that in response to external stimuli, mice exhibit increased oxidative stress factors, leading to signi cant elevations in biochemical markers such as TBIL, lactate dehydrogenase (LDH), creatinine (CRE), and blood urea nitrogen (BUN), which can promote tumor initiation and progression 30 31 .…”
Section: Discussionmentioning
confidence: 99%
“… 28 Converting these “cold tumors” into “hot tumors” by altering the tumor immune microenvironment presented a significant challenge in the field of immunotherapy for metastatic CRC. 29 A previous study concluded combination therapy as a potential solution to overcome this limitation, particularly through the administration of antiangiogenic drugs, which might potentially provide amazing survival benefits for patients with metastatic CRC. 30 Notably, antiangiogenic drugs not only conferred the ability to enhance the tumor immune microenvironment but also suppressed the development of tumor neovascularization, thereby achieving a synergistic action with immunotherapy.…”
Section: Discussionmentioning
confidence: 99%